Módulo web para el control de asistencia de los estudiantes de la Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López - Anzules Reyna, Marcos Cristhian (2015)
The objective of this work was to develop a attendance control web module for the Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López, as a requirement of the Internal Evaluation Committee. It was performed in order to optimize the processes of delivering monthly reports, improving the quality and presentation of data. The application programming was developed in language C# with Visual Studio 2012 as IDE for the realization of the graphics that is displayed to the user and the SQL Server 2008 R2 management system database for handling data and various computer tools for optimal system. MIDAS agile methodology was also used for the various stages of application development. The results show an optimized delivery time of 99.80%, allowing it to streamline the process of data analysis for studies of student absenteeism and verify compliance with the workflow of teachers.